Analyzing Smart Contracts With MadMax. - Livshits, Benjamin (Communications of the ACM, 2020)
The article discusses using the computer program MadMax to analyze smart contracts, Internet financial contracts which are supposed to embrace computational integrity, often using blockchain-based systems such as Ethereum Virtual Machine (EVM) and similar systems. It explores unique features of MadMax such as metering, static analysis, and its ability to perform a permanent denial-of-service for out-of-gas attacks on contracts.